1992
DOI: 10.2331/suisan.58.509
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Levels of n-3 Highly Unsaturated Fatty Acids in Diet for Fingerlings of Red Sea Bream.

Abstract: This experiment was conducted to confirm the relationship between dietary lipid levels and n-3 highly unsaturated fatty acids (n-3HUFA) contents and to determine a suitable n-3HUFA content in diet for fingerlings of red sea bream by feeding them with various white fish meal-casein diets containing different amounts of lipid (5-20%) and n-3HUFA (1.2-4.2%) at a fixed protein level of 52%.At a level of 10% lipid, growth was lowered as n-3HUFA content in the diet increased, and the lowest feed performances were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 0 publications
4
29
0
Order By: Relevance
“…It has also been suggested that the EFA requirement in marine fish should be calculated in percent of lipid rather than in percent of diet. In red sea bream and yellowtail the EFA requirement has been estimated at 20% n-3 HUFA of dietary lipid (Takeuchi et al 1992a; while 10% seems sufficient in red drum (Sciaenops ocellatus) (Lochmann and Gatlin 1993). Regardless of species, 22:6n-3 appears to be the primary EFA followed by 20:5n-3.…”
Section: Marine Fishmentioning
confidence: 99%
“…It has also been suggested that the EFA requirement in marine fish should be calculated in percent of lipid rather than in percent of diet. In red sea bream and yellowtail the EFA requirement has been estimated at 20% n-3 HUFA of dietary lipid (Takeuchi et al 1992a; while 10% seems sufficient in red drum (Sciaenops ocellatus) (Lochmann and Gatlin 1993). Regardless of species, 22:6n-3 appears to be the primary EFA followed by 20:5n-3.…”
Section: Marine Fishmentioning
confidence: 99%
“…On the other hand, the amount of essential fatty acids (EFA), such as linolenic acid and n-3HUFA, required to achieve maximum growth is known to increase along with increase in the dietary lipid level in rainbow trout and red sea bream. 2,3) This experiment was, therefore, conducted to confirm the relationship between dietary lipid levels and n-3HUFA contents, and to determine a suitable n-3HUFA content in the diet for fingerlings of yellowtail, by feeding them with various white fish meal diets containing different amounts of lipid (6-20%) and n-3HUFA (1.5-5.2%) at a fixed protein level of 50%. Four levels of lipid in diet were prepared, and at each lipid level, 1.5-5.2% of n-3HUFA were added at a fixed protein level of 50% which was suggested to be suitable in the previous experiment.1) These experimental diets were supplied to fish in dry pellet form.…”
mentioning
confidence: 99%
“…No statistically significant differences were observed in growth (SGR and WG) and feed utilization parameters among different treatments, whereas, in other sparid species, the best growth performance in juvenile P. major [126] and juvenile S. aurata [127] was reported to occur at a DHA/EPA ratio of 0.5. However, in the study from Mozanzadeh et al [125], SGR and FCR values in S. hasta juveniles were not affected by different dietary DHA/EPA ratios, possibly reflecting species-specific differences with regard to P. major [113] and S. aurata [126]. These results in S. hasta suggested that either fatty acid (DHA or EPA) was able to meet the essential fatty acid requirements, if sufficient total n-3 LC-PUFAs were supplied in the diet.…”
Section: Growth Performancementioning
confidence: 78%
“…In this context, most of the studies conducted in marine carnivorous fish species so far established an optimal dietary n-3 LC-PUFA requirement of 0.5%-2% of dietary DM [7]. Regarding sparids, the minimum requirement in dietary n-3 LC-PUFAs (DHA + EPA) required for optimal growth and development in juveniles has been reported to be about 1.0 in S. aurata [111], 1.3 in silver seabream, Rhabdosargus sarba [112] and 3.7 in P. major [113]. In S. hasta, the optimum dietary level of n-3 LC-PUFA in juveniles (BW i = 13.3 ± 0.1g) was determined in a nutritional study using five isonitrogenous (ca.…”
Section: Requirements Of N-3 Long Chain Polyunsaturated Fatty Acidsmentioning
confidence: 99%